2013
DOI: 10.1007/s10096-013-1854-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of bacterial communities on the inner and outer surfaces of peripheral venous catheters

Abstract: Peripheral venous catheters (PVCs) are some of the most widely used medical devices in hospitals worldwide. PVC-related infections increase morbidity and treatment costs. The inner surfaces of PVCs are rarely examined for the population structure of bacteria, as it is generally believed that bacteria at this niche are similar to those on the external surface of PVCs. We primarily test this hypothesis and also study the effect of antibiotic treatment on bacterial communities from PVC surfaces. The inner and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
0
9
1
Order By: Relevance
“…The overall bacterial diversity observed in this study was less than that reported in other studies [ 17 , 31 ]. The samples in the study were taken from patients under clinical care, including use of 2% chlorhexidine gluconate in alcohol, to decontaminate skin sites prior to PIVC insertion.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The overall bacterial diversity observed in this study was less than that reported in other studies [ 17 , 31 ]. The samples in the study were taken from patients under clinical care, including use of 2% chlorhexidine gluconate in alcohol, to decontaminate skin sites prior to PIVC insertion.…”
Section: Discussioncontrasting
confidence: 97%
“…Methylobacterium spp., was the dominant genera on both the PIVC tips and skin swabs. This contrasts to other studies which have reported Stenotrophomonas spp., as the major species recovered from PIVCs [ 17 ], and Staphylococcus spp. and Corynebacterium spp., as the major species recovered from skin [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial growth leads to separation between valve and tissue resulting in paravalvular leakage [72,73]. Peripheral venous catheter (PVC) infections [74] and central venous catheter (CVC) infections [75] mostly result in IE.…”
Section: Infective Endocarditis (Ie)mentioning
confidence: 99%